The Pathology of Type II Modic Changes: Fat Deposition or Osteosclerosis? A Study Using CT Scan - Sun, Chi (Biomed Res Int, 2018)
STUDY DESIGN: A retrospective cross-sectional study of type II Modic changes (MCs). OBJECTIVE: To evaluate the CT values of type II MCs and determine their relationship with disc degeneration. METHODS: 124 type II MCs from 66 patients' MRI and CT were included and analyzed. Disc degeneration adjacent to MCs was evaluated based on Pfirrmann classification. CT values of bone marrow area and endplate from MC regions, adjacent non-MC regions, and L1 vertebra were measured. CT value changes (ΔCT value) were defined as MCs' CT value minus non-MCs'. According to the types of variables, paired t-test, signed-rank test, two-way ANOVA, and Friedman test were used. RESULTS: The CT value of MCs was significantly higher than that of non-MCs at both bone marrow area and endplate (P<0.0001, resp.). Good consistency was found between non-MCs and L1 vertebra in the CT value of bone marrow area and endplate (P=0.2129, P=0.2272, resp.), suggesting the control group was valid. Adjacent to type II MCs, there were 8 (6.4%) discs with grade III degeneration, 58 (46.8%) with grade IV, and 58 (46.8%) with grade V. The ΔCT value of grade V disc degeneration was larger than that of grade IV at the endplate (P=0.0150). CONCLUSIONS: Osteosclerosis may exist in type II MCs. The more severe the degeneration of the adjacent disc, the greater the degree of osteosclerosis.